The Role of Deliberation in Correcting and Validating Intuition: A Holy Grail for Child-care Professionals or a False Dawn? - Heron, Gavin; Black, Kate (British Journal of Social Work, 2025)
The role of deliberation in correcting and validating the more error prone intuition is subject to much interest and debate across a range of professions and disciplines. For child-care professionals, the opportunity to correct errors in their reasoning is crucial, especially where serious consequences can arise from mistakes. This study examines the way deliberation corrects and validates intuition when professionals discuss vulnerable children who have experience of secure care and present a serious risk of harm to other people. Data from twenty-one consultation meetings involving eighty-one professionals are collected and coded. Findings suggest that professionals engage in deliberative thinking to validate intuitive ideas, which is important in providing explanations and justifications. However, deliberation is rarely used to correct errors in intuitive thinking and this gives some cause for concern about the quality of professionals' reasoning in complex child-care cases. Child-care professionals should give greater consideration to their reasoning, especially the role of deliberative thinking in complex cases and where serious risks exist for children. This requires professionals to value errors in, and challenges to their own thinking and recognise the additional cognitive effort necessary for deliberation.